Managing weeds in rice (Oryza sativa)-wheat (Triticum aestivum)-greengram (Vigna radiata) system under conservation agriculture in black cotton soils - SINGH, V P; BARMAN, K K; SINGH, P K; SINGH, RAGHWENDRA; DIXIT, ANIL (The Indian Journal of Agricultural Sciences, 2017)
Conservation agriculture (CA) does have several advantages over conventional tillage (CT) based agriculture in terms of soil health parameters. However, weeds are the major biotic constraint in CA, posing as a great challenge towards its adoption. Field experiment was conducted at Directorate of Weed Research , Jabalpur (MP) during 2012–14 to monitor weed dynamics, crop productivity, and soil health parameters in a rice (Oryza sativa L.)-wheat (Triticum aestivum L.)-greengram [Vigna radiate (L.) Wilczek] cropping sequence under CA system. The treatments consist of ZT (DSR)+Sesbania brown manuring – ZT (wheat) – ZT (greengram), with or without crop residue cover; CT (DSR)+Sesbania brown manuring – CT (wheat) – ZT (green gram), with or without crop residue cover; farmers practice, i.e. CT (TPR) – CT (wheat). The lowest total weed density was recorded under ZT (DSR)+Sesbania. Compared to CT, significantly lower density of Cyperus iria, but higher density of Caesulia axillaris was recorded under ZT; while CT (TPR) recorded the lowest population of P. minima and D. retroflexa during rice. Similarly, in wheat, significantly lower population of Phalaris minor and Chenopodium album was noticed under ZT. Highest grain yield (3.42 t/ha) was recorded with transplanted rice; whereas, higher yield of wheat was recorded when sown after DSR and crop residues were recycled. Tillage systems did not differ significantly in terms of soil respiration rate when crop residues were recycled. There was significant gain in soil organic carbon pool only when the complete conservation package of ZT along with crop residue recycling was adopted. A preliminary survey conducted in the adjoining localities of Jabalpur during 2012-13 showed lack of awareness among the farmers about the resource conservation technology (RCT) to grow wheat. Subsequently, the trials laid out in 3 farmers’ field during rabi seasons of 2012-13 and 2013-14 also showed that wheat performed much better under CA, as compared to the conventional farmers’ practice, resulting in lower cost of production, higher income and higher benefit: cost ratio. Green gram, sown with RCTs and chemical weed control measure in the same farmers’ fields following wheat, also provided higher B:C ratio and an additional net return of `28 975/ha over farmers practice. It was concluded that the RCTs like ZT and residue cover could be practiced in the black cotton soils to increase farmers’ income.